Peningkatan Pengetahuan dan Keterampilan Kader Melalui Pemberdayaan Pembuatan Lotion Anti Aedes aegypti Dari Ekstrak Daun Pandan Wangi (Pandanus Amaryllifolius Roxb.) Di Rw. 11 Kelurahan Cibeureum Kecamatan Cimahi Selatan Kota Cimahi - Hanurawaty, Neneng Yety; Djuhriah, Nany; Fikri, Elanda (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Dengue Hemorrhagic Fever (DHF) remains a significant public health problem in Indonesia, including Cimahi City. One preventive measure that can be implemented is community empowerment in vector control, using natural ingredients to make mosquito-repellent lotion. This community service initiative aims to improve the knowledge and skills of cadres in preparing an anti-mosquito lotion using pandan leaf extract (Pandanus amaryllifolius Roxb.). Method: Participants in the community service activities are cadres in RW 11, ​​Cibeureum Village, South Cimahi District, Cimahi City. Preparation Stage: processing RW and Puskesmas permits, site surveys, and preparation of tools and materials. The implementation stage includes: socialization, counseling, interviews with cadres, RW deliberations, and practice making anti-mosquito lotion from fragrant pandan leaf extract. Results: The knowledge of cadres about knowledge of Dengue Hemorrhagic Fever (DHF) before counseling was 6 people in the good category (30%), 7 people in the sufficient category (35%), and 7 people in the less category (35%), and after counseling, as many as 20 people in the good category (100%). The cadres' skills in making anti-mosquito lotion before mentoring were 61.75%, and after mentoring, 95.25% [A1], indicating an increase of 33.5%. Conclusion: This activity effectively improved the knowledge and skills of cadres in RW 11, Cibeureum Village. The cadres gained a better understanding of the dangers of dengue fever and its prevention, and were able to independently produce a natural lotion as an alternative to mosquito control.